Early infantile epileptic encephalopathy associated with a high voltage gated calcium channelopathy. Issue 2 (20th January 2013) - Edvardson, Simon; Oz, Shimrit; Abulhijaa, Fida Aziz; Taher, Flora Barghouthi; Shaag, Avraham; Zenvirt, Shamir; Dascal, Nathan; Elpeleg, Orly
Abstract : Background: Early infantile epileptic encephalopathies usually manifest as severely impaired cognitive and motor development and often result in a devastating permanent global developmental delay and intellectual disability. A large set of genes has been implicated in the aetiology of this heterogeneous group of disorders. Among these, the ion channelopathies play a prominent role. In this study, we investigated the genetic cause of infantile epilepsy in three affected siblings. Methods and results: Homozygosity mapping in DNA samples followed by exome analysis in one of the patients resulted in the identification of a homozygous mutation, p.L1040P, in the CACNA2D2 gene. This gene encodes the auxiliary α2 δ2 subunit of high voltage gated calcium channels. The expression of the α2 δ2-L1040P mutant instead of α2 δ2 wild-type (WT) in Xenopus laevis oocytes was associated with a notable reduction of current density of both N (CaV 2.2) and L (CaV 1.2) type calcium channels. Western blot and confocal imaging analyses showed that the α2 δ2-L1040P mutant was synthesised normally in oocyte but only the α2 δ2-WT, and not the α2 δ2-L1040P mutant, increased the expression of α1B, the pore forming subunit of CaV 2.2, at the plasma membrane. The expression of α2 δ2-WT with CaV 2.2 increased the surface expression of α1B 2.5–3 fold and accelerated current inactivation, whereas α2 δ2-L1040P did not produce any of these effects. Conclusions: L1040P mutation in the CACNA2D2 gene is associated with dysfunction of α2 δ2, resulting in reduced current density and slow inactivation in neuronal calcium channels. The prolonged calcium entry during depolarisation and changes in surface density of calcium channels caused by deficient α2 δ2 could underlie the epileptic phenotype. This is the first report of an encephalopathy caused by mutation in the auxiliary α2 δ subunit of high voltage gated calcium channels in humans, illustrating the importance of this subunit in normal physiology of the human brain.